FtsZ-mediated spatial–temporal control over septal cell wall synthesis - Longhua Hu; Amilcar J. Perez; Tanya Nesterova; Zhixin Lyu; Atsushi Yahashiri; David S. Weiss; Jie Xiao; Jian Liu (Proceedings of the National Academy of Sciences, 2025)
FtsZ, the tubulin-like GTPase, is the central organizer of the bacterial divisome, a macromolecular complex that synthesizes new septal cell wall (made of septal peptidoglycan, sPG) to allow cell wall constriction and cytokinesis. In Escherichia coli , it was shown that 1) FtsZ recruits all essential divisome proteins to the septum, including the core sPG synthase complex, FtsWIQLB, and its activator, FtsN; 2) FtsWIQLB must complex with FtsN to be activated to synthesize sPG under the wildtype background; and 3) the Brownian ratcheting by treadmilling FtsZ polymers drives the directional movements of sPG synthase proteins along the septum circumference; and 4) FtsZ is essential for the early stage, but dispensable for the late stage of cell wall constriction. However, it remains unclear how FtsZ spatial–temporally organizes the divisome for robust cell wall constriction during cytokinesis. Combining theoretical modeling with experiments in E. coli , we show that at the early stage during cell division, the Brownian ratcheting by FtsZ treadmilling acts both as a template to corral FtsWIQLB and FtsN into close contacts for FtsWIQLB-FtsN complex formation and as a conveyor to maximally homogenize the septal distribution of sPG synthesis activities to avoid uneven cell wall constriction. When the septum constricts progressively, the FtsN septal density increases via binding to denuded sPG (dnG) and serves as the template to activate FtsWIQLB for continued sPG synthesis, rendering FtsZ dispensable. Our work suggests an overarching framework for how FtsZ spatial–temporally regulates septal cell wall constriction, in which different bacteria species may operate in various parameter regimes to meet their distinct functional requirements.